IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PEMBELAJARAN DARING BAGI PENDIDIKAN SEKOLAH DASAR SELAMA COVID-19 DI KECAMATAN LUBUK BASUNG, KABUPATEN AGAM TAHUN 2020 - Nisa Ulzikra; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The COVID-19 pandemic has had an impact on many parties, this condition has penetrated the world of education, the central government down to the regional level has issued a policy to close all educational institutions. This makes the government and related institutions must present an alternative educational process. The policy is in the form of a Circular of the Ministry of Education and Culture No. 4 of 2020 concerning Implementation of Education Policies in the Emergency Period of the Spread of COVID. Governor of West Sumatra Regulation Number 20 of 2020 concerning Guidelines for Large-Scale Social Restrictions (PSBB) in Handling Covid-19 in West Sumatra. Instruction of the Regent of Agam Number: 1528/Disdikbud-Ag/2020 concerning Handling the Impact of the Corona Virus in the Agam Regency Environment. Instruction of the Regent of Agam Number: 421/2445/Disdikbud/2020 concerning Extension of Time for Implementation of Study Activities and Ramadan Worship Activities at Home. Circular Letter of the Agam District Education Office Number: 421/1539/Disdikbud/2020 concerning the Prevention of Covid-19. The purpose of this study is to find out the Implementation of Government Policy in Online Learning for Elementary School Education During Covid-19 in Lubuk Basung District, Agam Regency in 2020. The theory used in this study is the implementation of George Edward III. This research uses a qualitative method with the type of research in the form of descriptive research. Data collection techniques in this study are interviews, observation and documentation. The results of the study explain that the implementation of online policies is still not optimal. Because the four variables that affect the success or failure of policy implementation are not fully implemented properly. And there are also many obstacles faced by the government, schools, parents and students. Therefore, the need for cooperation between policy makers, policy implementers and policy objectives so that they are more implemented. Keywords : Online learning communication, Online learning resources, Disposition of online learning, Online learning bireaucracy structure